Characterization of Regolith Types and its Impact on Gold Anomaly in Highly Weathered Terrains Using Multiple Dataset - Ntori, Clement; Arhin, Emmanuel; Sulemana, Ibrahim Abdul; Boateng, D. Y Antwi (International Journal of Geography and Geology, 2019)
Deposition of post mineralization materials and incessant evolution of regolith materials have resulted in many complex geological environments. These often produce subtle geochemical responses and make geochemical anomaly delineation very difficult. To mitigate the challenge of following ‘false’ anomaly emanating from the regolithic effect, the study mapped the regolith types and used it to explain the geochemical behavior of gold. Multiple dataset such as Aster, radiometric, GDEM were combined with ground truthing and evaluated to characterize the regolith into FRED. This was done alongside the collection of 3252 soil samples. The samples were analyzed for gold using BLEG with AAS finishing. The geochemical data were however interpreted accounting for the regolith. Multiple thresholds were chosen for each regolith using q-q plots. The results showed 24.3% to be depositional regolith and 75.7% was a residual environment consisting of 46% Ferruginous, 40% relict and 4% erosional. Both ferruginous and depositional regimes had capabilities of impacting negatively on gold anomaly. The result further showed that each regolith regime had capabilities of hosting mineralization and recommends that equal weight of importance should be accorded to all regimes. It further proposed that the regolith map should be fully integrated into geochemical data to avoid following ‘false’ anomalies.